2017
DOI: 10.1001/jamaophthalmol.2017.4030
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Ranibizumab With or Without Verteporfin Photodynamic Therapy for Polypoidal Choroidal Vasculopathy

Abstract: for the EVEREST II study group IMPORTANCE Polypoidal choroidal vasculopathy (PCV) is a common subtype of exudative age-related macular degeneration among Asian individuals. To our knowledge, there are no large randomized clinical trials to evaluate intravitreal ranibizumab, with and without verteporfin photodynamic therapy (vPDT), for the treatment of PCV.OBJECTIVE To compare the efficacy and safety of combination therapy of ranibizumab and vPDT with ranibizumab monotherapy in PCV. DESIGN, SETTING, AND PARTICI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
313
2
9

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 257 publications
(342 citation statements)
references
References 33 publications
11
313
2
9
Order By: Relevance
“…The improvement of 13 letters at 28 weeks in our study is at least comparable with the results of the VIEW 1 and 2 studies that demonstrated respective improvement of 7.8 and 8.9 letters in AMD [16]. These results are also comparable with those of combination therapy (ranibizumab + PDT) in the EVEREST and EVEREST II studies at 12 months (+10.9 and +8.3 letters, respectively) [12, 13]. On the other hand, ranibizumab monotherapy only demonstrated a 5-letter improvement in the LAPTOP study [10].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The improvement of 13 letters at 28 weeks in our study is at least comparable with the results of the VIEW 1 and 2 studies that demonstrated respective improvement of 7.8 and 8.9 letters in AMD [16]. These results are also comparable with those of combination therapy (ranibizumab + PDT) in the EVEREST and EVEREST II studies at 12 months (+10.9 and +8.3 letters, respectively) [12, 13]. On the other hand, ranibizumab monotherapy only demonstrated a 5-letter improvement in the LAPTOP study [10].…”
Section: Discussionsupporting
confidence: 88%
“…The Everest study showed that PDT alone or in combination with ranibizumab intravitreal injections (IVT) were both superior to sole ranibizumab therapy in achieving complete polyp regression (in 71.4, 77.8, and 28.6% of eyes, respectively) after 6 months of follow up [12]. The Everest study II confirmed that PDT in combination with ranibizumab IVT were superior to sole ranibizumab therapy in achieving complete polyp regression (69.3 vs. 34.7% of all eyes) after 12 months of follow-up [13]. However, complications may occur with PDT, including subretinal hemorrhage, retinal pigment epithelial (RPE) tears, and choroidal infarcts [14].…”
Section: Introductionmentioning
confidence: 99%
“…21 The EVEREST II study reported that combination therapy was superior to IVR monotherapy in terms of the 12-month visual outcomes and number of injections. 10 Thus, data regarding the long-term outcomes of these regimens are desirable.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the prospective, randomised, doublemasked, multicentre EVEREST II study showed that the 12-month VA was better for patients who received combination therapy of ranibizumab with PDT than for those who received ranibizumab alone. 10 However, the invasive effect of PDT on the retina and choroid remains concerning. 11 In clinical settings, anti-VEGF agents are often administered for PCV on a pro re nata (PRN) basis, with or without PDT.…”
Section: Introductionmentioning
confidence: 99%
“…Once PCV is diagnosed, combination therapy with photodynamic therapy (PDT) and intravitreal anti-VEGF injections may have a higher chance of improving vision and promoting regression of polyps, DOI: 10.1159/000481540 edema, and subretinal fluid while decreasing the number of intravitreal injections needed and overall treatment burden for these patients [10,11]. Due to this importance, PCV is becoming increasingly recognized in the world, not only in Asia, where PCV can occur in up to 50% of AMD patients [12][13][14], but also in Caucasian individuals, where the prevalence of PCV in eyes with exudative AMD can reach almost a quarter [15,16].…”
Section: Introductionmentioning
confidence: 99%